STUDI KASUS PEMENUHAN KEBUTUHAN OKSIGENASI DENGAN TEKNIK RELAKSASI NAFAS DALAM PADA PASIEN CONGESTIVE HEART FAILURE DI RUMAH SAKIT TK II PUTRI HIJAU MEDAN TAHUN 2016 - Purba, Lermiana; Susyanti, Deni; Pamungkas, Pamungkas (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2016)
Congestive heart failure is the incapacity of heart to pump adequate blood in fulfilling the need for oxygen ad nutrients which causes cardiac output to decrease which brings about pain in chest. Pain management can be done by using pharmacological and non-pharmacological therapies. Deep breath relaxation therapy is done in the non-pharmacological nursing pain management. It will increase the supply of oxygen to tissues so that pain will decrease. The research used descriptive method with case study design which was aimed to find out the description of the need for oxygen in congestive heart failure patients. The nursing approach consisted of nursing analysis, diagnosis, intervention, implementation, and evaluation in 2 clients with the same case. The result showed that in case I there was no more pain in chest in the third day of nursing, while in case II complaint about short of breath could be handled in the third day of nursing since the client felt relaxed. The conclusion was that the need for oxygen could be handled by using deep breath relaxation technique. It is recommended that the clients and their families comply with doing deep breath relaxation technique.